2010
DOI: 10.1111/j.1472-765x.2010.02900.x
|View full text |Cite
|
Sign up to set email alerts
|

The synergy of honokiol and fluconazole against clinical isolates of azole-resistant Candida albicans

Abstract: Aims:  To evaluate the interaction of fluconazole (FLC) and honokiol (HNK) in vitro and vivo against azole‐resistant (azole‐R) clinical isolates of Candida albicans. Methods and Results:  A checkerboard microdilution method was used to study the in vitro interaction of FLC and HNK in 24 azole‐R clinical isolates of C. albicans. In vivo antifungal activity was performed to further analyse the interaction between FLC and HNK. In the in vitro study, synergism was observed in all 24 FLC‐resistant strains tested as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 23 publications
2
24
0
Order By: Relevance
“…). In the current reports, honokiol has been demonstrated to augment and exhibit a synergism with chemotherapeutic agents including rapamycin, gemcitabine, fluconazole and imatinib . Moreover, in animal models, our study and others show no obvious impacts in pathologic changes and genotoxicity after honokiol treatment, suggesting that honokiol is safe in animals and thus could be applicable in clinical practice.…”
Section: Discussionsupporting
confidence: 54%
“…). In the current reports, honokiol has been demonstrated to augment and exhibit a synergism with chemotherapeutic agents including rapamycin, gemcitabine, fluconazole and imatinib . Moreover, in animal models, our study and others show no obvious impacts in pathologic changes and genotoxicity after honokiol treatment, suggesting that honokiol is safe in animals and thus could be applicable in clinical practice.…”
Section: Discussionsupporting
confidence: 54%
“…Jin et al reported the synergy of honokiol and FLC against isolates of azole-resistant C. albicans. In their report, honokiol MICs were 64-128 lg ml À1 against FLC-resistant C. albicans (Jin et al 2010). These differences might be due to the high degree of FLC resistance and thus manifest as a cross-resistance to honokiol and FLC.…”
Section: Discussionmentioning
confidence: 95%
“…In their report, honokiol MICs were 64–128 μ g ml −1 against FLC‐resistant C. albicans (Jin et al . ). These differences might be due to the high degree of FLC resistance and thus manifest as a cross‐resistance to honokiol and FLC.…”
Section: Discussionmentioning
confidence: 97%
“…[3] Unfortunately, however, the effective use of fluconazole has been limited significantly by the development of azole resistance, which has been attributed to the failure of antifungal treatments in the clinic. [4][5][6] One promising approach aimed at overcoming azole resistance has been reported that involves sensitizing C. albicans toward fluconazole with small molecules, including piperazinyl quinolines, [7] amiodarone, [8] tacrolimus, [9] honokiol, [10] and Allicin. [11] The recent screening of a natural product library in our research group revealed berberine (1) as the most active synergist in a series of antifungal agents, including fluconazole, [12] ketoconazole, amphotericin B, and miconazole.…”
Section: Introductionmentioning
confidence: 99%